Strategies for Filariasis Prevention in Indonesia Based on Community Behavior and Compliance: A Review - Nadia Dwihajra Musrin (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2025)
Background: Filariasis remains a significant public health problem in endemic areas, driven by environmental conditions that support vector proliferation, limited community knowledge, and low compliance with prevention programs. Objective: To identify and analyze factors influencing the incidence and prevention of filariasis in Indonesia, drawing on evidence from previous studies. Methods: A literature review was conducted by analyzing 10 relevant peer-reviewed scientific journals. Results: Evidence indicates that community compliance with mass drug administration (POPM) and preventive behaviors against filariasis remains low in many regions. Key influencing factors include knowledge levels, attitudes, trust in health workers, social support, and environmental conditions. Conclusion: Effective filariasis prevention requires sustained efforts focusing on community education, environmental improvement, and strengthening the role of health workers, with strategies tailored to local contexts. Keywords: Filariasis, prevention behavior, community compliance